Expansion of photovoltaic technology (PV) as a solution for water energy nexus in rural areas of Iran: Comparative case study between Germany and Iran - Carl-Anton von Heyking; Tinoush Jamali Jaghdani (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2017)
Iran is suffering from groundwater resources depletion through the excessive subsidized electricity for water pumping and the resulting disproportionate water consumption in agriculture. The creation of an alternative income sources for farmers and elimination of heavy subsidies for groundwater pumping simultaneously is a possible option for dealing with this threat. By expanding photovoltaic technology (PV) in rural areas, farmers can have an alternative source of income by supply and sale of renewable energy through feed-in tariff (FiT) mechanism. The latest decision of the Ministry of Energy in Iran in 2016 for purchasing electricity which is generated by low capacity PV owners can be a solution for the above mentioned problem. This study undertakes a comparison between Germany and Iran of the development of decentralized power system and PV expansion by private owners. In direct comparison to Germany, Iran has a far higher solar radiation and significant potential for the generation of electricity through PVs. This study illuminates both countries' costs of conventional/renewable electricity power, their changing FiT's for renewable power and the renewable energy laws. Comparing the price development shows that a lucrative business arises by selling electricity for the Iranian owners of PV whereas in Germany the trend of self-consumption is clearly preferred. Innovative policies are needed to tackle infrastructural and economic challenges to exploit this potential in Iran.
Keywords: 330; Iran; Germany; photovoltaic technology (PV); groundwater depletion; electricity subsidy; feedintariff (FiT); decentralized power system; renewable energy laws